2019
DOI: 10.1002/pssa.201900380
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Complete Elimination of Size‐Dependent Efficiency Decrease in GaN Micro‐Light‐Emitting Diodes

Abstract: Herein, a successful elimination of the size-dependent efficiency decrease in GaN micro-light-emitting diodes (micro-LEDs) is achieved using damage-free neutral beam etching (NBE). The NBE technique, which can obtain ultralow-damage etching of GaN materials, is used in place of the conventional inductively coupled plasma to form the micro-LED mesa. It is found that all the fabricated micro-LEDs with sizes ranging from 40 to 6 μm show external quantum efficiency (EQE) versus current density characteristics simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…[62,63] Surface passivation via atomic layer deposition, wet chemical etching with KOH or (NH 4 ) 2 S, and neutral beam etching have been shown to be efficient methods for suppressing leakage current and surface defects, leading to size-independent peak EQE. [60,[63][64][65][66][67][68] As a result, blue InGaN Micro-LEDs demonstrated >40% EQE in the size range of 10-100 µm, [60] while the peak EQEs of AlGaInP Micro-LEDs remained less than 12%. Thus, for the optimal design of full-color Micro-LED displays, different size chips should be used for each color, leading to highly complex drive circuit designs.…”
Section: Full-color Color-conversion Micro-led Arraysmentioning
confidence: 99%
“…[62,63] Surface passivation via atomic layer deposition, wet chemical etching with KOH or (NH 4 ) 2 S, and neutral beam etching have been shown to be efficient methods for suppressing leakage current and surface defects, leading to size-independent peak EQE. [60,[63][64][65][66][67][68] As a result, blue InGaN Micro-LEDs demonstrated >40% EQE in the size range of 10-100 µm, [60] while the peak EQEs of AlGaInP Micro-LEDs remained less than 12%. Thus, for the optimal design of full-color Micro-LED displays, different size chips should be used for each color, leading to highly complex drive circuit designs.…”
Section: Full-color Color-conversion Micro-led Arraysmentioning
confidence: 99%
“…Recently, it has been reported that chemical treatment and sidewall passivation eliminate the size‐dependent efficiency decrease for μ‐LEDs with a size down to 10 μm. [ 7,8 ] However, μ‐LEDs with a size smaller than 10 μm still suffer severe efficiency loss even with chemical treatments and passivation. [ 6 ] The previous studies have shown that the decreased EQE of μ‐LEDs with size was attributed to the increased nonradiative surface recombination with decreasing size.…”
Section: Figurementioning
confidence: 99%
“…[18,19] So far, a few methods have been attempted for removing the sidewall damage induced by the dry-etching, such as neutral beam etching and KOH chemical treatment. [25,26] Though they have demonstrated to be effective in mitigating the etching damage, the etching approach to fabrication of μLEDs still requires a sidewall passivation and isolation, which can bring about extra processing and performance issues as well. [20,21] Recently, we have developed a different approach to fabrication of InGaN/GaN multiquantum wells (MQWs) μLEDs: a selective overgrowth on patterned templates instead of mesa-etching.…”
Section: Introductionmentioning
confidence: 99%
“…The green μLEDs have demonstrated high external quantum efficiency and high luminescence. [3,25] We have also grown InGaNbased HEMT-μLEDs to take advantage of higher driving current densities expected of μLEDs for VLC. [7] In this work, currentvoltage and capacitance-voltage characteristics have been investigated systematically on the overgrown μLEDs with different sizes, which have also been compared with those μLEDs fabricated by means of using a conventionally dry-etching approach.…”
Section: Introductionmentioning
confidence: 99%